2016
DOI: 10.3390/ijms17091518
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Immune Defence Mechanisms of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) against Entomopathogenic Fungal Infections

Abstract: Insects infected with entomopathogenic fungi, experience physiological changes that influence their growth and immune defence. The potential of nine isolates of entomopathogenic fungi was evaluated after determining percent germination and relative conidial hydrophobicity. However, nutritional indices were evaluated after immersing eighth-instar Rhynchophorus ferrugineus larvae into each isolate suspension (1 × 10 7 conidia/mL). The results showed that isolates B6884 and M9374 had 44.51% and 39.02% higher coni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 27 publications
9
40
0
Order By: Relevance
“…The present study revealed that all isolates exhibited more than 96% conidial viability (F = 0.36; df = 2, 12; P = 0.708), even from the least virulent studied isolate 7234. These findings are in agreement with previous studies indicating that low virulence among highly viable isolates of fungi reflects that virulence is regulated by multiple sets of traits (Hussain et al 2015 andHussain et al 2016). In the present study, significant differences (F = 101; df = 2, 12; P < 0.0001) in Pr1 activity in all of the studied EPF isolates were also recorded.…”
Section: Pathogen Virulencesupporting
confidence: 93%
“…The present study revealed that all isolates exhibited more than 96% conidial viability (F = 0.36; df = 2, 12; P = 0.708), even from the least virulent studied isolate 7234. These findings are in agreement with previous studies indicating that low virulence among highly viable isolates of fungi reflects that virulence is regulated by multiple sets of traits (Hussain et al 2015 andHussain et al 2016). In the present study, significant differences (F = 101; df = 2, 12; P < 0.0001) in Pr1 activity in all of the studied EPF isolates were also recorded.…”
Section: Pathogen Virulencesupporting
confidence: 93%
“…Tenth-instar R. ferruginous larvae fed on a coumarin-containing diet showed the least efficacy of conversion of ingested (ECI), and digested (ECD) diet, which meant that less food was available for growth because most of the energy was metabolized for host defense. Similar nutritional indices patterns of ECD and ECI in red palm weevil larvae were reported, when larvae were dipped in conidial suspensions of entomopathogenic fungi [ 4 , 5 ], or larvae fed on diets incorporated with synthetic pesticides [ 3 ]. Such tremendous reductions in ECI (70.04%), and ECD (78.39%) by coumarin compared to control larvae observed in the current study revealed that most of the energy from ingested food is being used to perform physiological activities to combat the toxin (coumarin), which means that less food is being utilized for larval growth and development.…”
Section: Discussionsupporting
confidence: 52%
“…Different environmental friendly strategies including entomopathogenic fungi [ 4 , 5 , 6 ], nematodes [ 7 ], bacteria [ 8 , 9 ], development of pheromone traps [ 10 , 11 , 12 , 13 ], sterile insect technique [ 14 , 15 , 16 , 17 ], and plant based insecticides [ 18 , 19 , 20 , 21 ] remained the subject of previous research investigations. Among them, plant-based products especially plant secondary metabolites are the most promising alternatives to environmental deteriorating insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…These compatible interactions at all tested doses of 1-Chlorooctadecane enabled us to support the choice for their simultaneous use in different proportions against date palm dust mites. The search on such a pairing remained a novel option against numerous pest species in order to circumvent slow and low mortality criticism of mycopathogen [23,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that both the fungi and plant secondary metabolites demonstrated an entirely different mode of actions to overcome the target host defense mechanisms to cause mortality. Fungal infection evades the host defense mechanism by triggering complex biochemical interactions in the form of series of events through cuticle adhesion, penetration, proliferation, and toxin production, which ultimately lead to the host mortality [29,[31][32][33]. On the other hand, plant secondary metabolites are known antagonists that act by interfering with the signaling of the nervous and cellular systems to overcome the target host defense mechanism [34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%